Studies on experimental models - Basu, Samar. (Oxidative stress in applied basic research and clinical practice, 2011)
There is a widespread consensus that use of antioxidants as a therapeutic approach may counteract free radical mediated pathologies. However, the role of antioxidants in normal physiology and redox signaling is still in its infancy. Since oxidative stress is related to various diseases and pathologies, scientists are eager to study the disease in humans, but it is not always ethical to study all the aspects of the disease in humans. Thus, it becomes mandatory to study the disease process and the mechanisms behind it through experimental models which generally involve animals, in vitro/cell culture studies, primates and even humans to a certain extent. Studies on Experimental Models contains data on the experimental models or review of such models of oxidative stress in various diseases. It is structured into six sections, which are as follows: diabetes, cardiovascular, neurology, ocular diseases, toxicology/environmental and in vitro/tissue culture. Each section presents a sketch of models in humans, animals and in vitro methods. Taken together, they comprise a valuable reference for basic and clinical scientists, one aimed at contributing to the advancement of oxidative stress research using appropriate animal models. DIABETES -- Role of Oxidative Stress and Targeted Antioxidant Therapies in Experimental Models of Diabetic Complications -- Experimental Models of Oxidative Stress Related to Cardiovascular Diseases and Diabetes -- CARDIOVASCULAR -- Arachidonic Acid Metabolism and Lipid Peroxidation in Stroke: Alpha-tocotrienol as a Unique Therapeutic Agent -- Assessment of Oxidative Stress in the Brain of Spontaneously Hypertensive Rat and Stroke-Prone Spontaneously Hypertensive Rat Using by Electron Spin Resonance Spectroscopy -- Small Heat Shock Proteins and Doxorubicin-induced Oxidative Stress in The Heart -- Oxidative Stress in Cardiovascular Disease: Potential Biomarkers and Their Measurements -- In vivo Imaging of Antioxidant Effects on NF-kappaB Activity in Reporter Mice -- NEUROLOGY -- MPTP and Oxidative Stress: It’s Complicated! -- Oxidative Stress in Alzheimer´s Disease: A Critical Appraisal of the Causes and the Consequences -- Retinal Disturbances in Patients and Animal Models with Huntington’s, Parkinson’s and Alzheimer’s Disease -- Stress Gene Deregulation in Alzheimer Peripheral Blood Mononuclear Cells -- The Use of Gpx4 Knockout Mice and Transgenic Mice to Study the Roles of Lipid Peroxidation in Diseases and Aging -- An Experimental Model of Myocardial and Cerebral Global Ischemia and Reperfusion -- OCULAR DISEASES -- Neovascular Models of the Rabbit Eye Induced by Lipid Hydroperoxide -- Purinergic Signaling Involved in the Volume Regulation of Glial Cells in the Rat Retina: Alteration in Experimental Diabetes -- TOXICOLOGY / ENVIRONMENTAL -- Helicobacter Pylori-induced Oxidative stress and Inflammation -- Experimental Models for Ionizing Radiation Research -- Experimental Models to Study Cigarette Smoke-Induced Oxidative Stress In Vitro and In Vivo in Pre-Clinical Models, and in Smokers and Patients with Airways Disease -- Exhaled Breath Condensate Biomarkers of Airway Inflammation and Oxidative Stress in COPD -- Induction of Oxidative Stress by Ascorbate in Isolated Mitochondria and by UV Irradiation in Human Skin -- Carbon Tetrachloride Induced Hepatotoxicity: A Classical Model of Lipid Peroxidation and Oxidative Stress -- Enhanced Urinary Excretion of Lipid Metabolites Following Exposer to Structurally Diverse Toxicants: A Unique Experimental Model for the Assessment of Oxidative Stress -- Oxidative Stress in Animal Models with Special Reference to Experimental Porcine Endotoxemia -- Models and Approaches for the Study of Reactive Oxygen Species Generation and Activities in Contracting Sketetal Muscle -- Exercise as a Model to Study Interactions Between Oxidative Stress and Inflammation -- Excercise as a Model to Study Oxidative Stress -- IN VITRO/TISSUE CULTURE -- Models of Mitochondrial Oxidative Stress -- Protection of Oxidant-Induced Neuronal Cells Injury by A Unique Cruciferous Nutraceutical -- Oxidatively Generated Damage to DNA and Biomarkers -- Measuring Oxidative Stress in Cell Cultures, Animals and Humans- Analysis and Validation of Oxidatively Damaged DNA -- The Roles of cAMP and G Protein Signaling in Oxidative Stress-Induced Cardiovascular Dysfunction -- Cellular and Chemical Assays for Discovery of Novel Antioxidants in Marine Organisms -- Arsenic-Induced Oxidative Stress: Evidence on In Vitro Models of Cardiovascular, Diabetes Mellitus Type 2 and Neurodegenerative Disorders.